Climate Change Education (CCE) Learning Approach as a Framework For Sustainability Education - Luthfia, Syarifatul Luthfia (Sekolah Pascasarjana Universitas Ibn Khaldun Bogor, 2025)
Earth society has been facing a very complex problem, namely climate change. Climate change has had a huge impact on life such as water crisis, natural disasters, health problems, food scarcity, and other socio-economic problems. Within the UNESCO framework, climate action is one of the thematic priorities of education for sustainable development. Education is a strategic sector to conduct climate change transformation education so that students grow as individuals who have the knowledge, skills and attitudinal values to respond to climate change. The purpose of this study is to review approaches to implementing climate change education in primary and secondary schools from different countries. This study used a systematic literature review method to collect and analyse data from 28 articles relevant to the topic under study. Results of the study classified various of approaches overview, there are curriculum, professional development, learning model, interdicipliner, project, and community approach. This research shows that climate change education involves not only students and teachers but also the local community. The implications of the results of this study are useful for the development of climate change education as sustainability education.